2014
DOI: 10.5539/ijc.v6n1p71
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic Properties and Structural Studies of Copper(II) Complexes of 2-Substituted-1,3-Diphenyl-1,3-Propanedione, Their 2,2'-Bipyridine and 1,10-Phenanthroline Adducts

Abstract: The complexes of 2-substituted-1,3-diphenyl-1,3-propanedione with copper(II) ion and their 2,2′-bipyridine and 1,10-phenanthroline adducts were synthesised and characterised by microanalysis, conductance, magnetic and spectral measurements. The conductance data showed that [Cu(dbm)(phen)](dbm) and [Cu(Me-dbm)(phen)](Me-dbm) are 1:1 electrolytes. The infrared spectra revealed the different shifts of the carbonyl frequency. While the electronic solid reflectance spectra of the prepared complexes exhibited three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Assignments of the infrared bands were made by comparing the spectra of the compounds with those already reported in the literature on similar systems (Omoregie, 2012;Omoregie et al, 2018). Literature review has shown that infrared spectra of β-diketones shows an appreciable coupling of different vibrational modes due to overlap of absorption frequencies (Nakamoto et al, 1961, Woods et al;2009a;Woods et al, 2009b;Omoregie et al, 2014;Omoregie and Woods, 2011). The metal-free ligand, HL, which consists of the uncoordinated C=O+C=C stretching vibrations has a double band in the 1603-1516 cm -1 region.…”
Section: Infrared Spectramentioning
confidence: 99%
“…Assignments of the infrared bands were made by comparing the spectra of the compounds with those already reported in the literature on similar systems (Omoregie, 2012;Omoregie et al, 2018). Literature review has shown that infrared spectra of β-diketones shows an appreciable coupling of different vibrational modes due to overlap of absorption frequencies (Nakamoto et al, 1961, Woods et al;2009a;Woods et al, 2009b;Omoregie et al, 2014;Omoregie and Woods, 2011). The metal-free ligand, HL, which consists of the uncoordinated C=O+C=C stretching vibrations has a double band in the 1603-1516 cm -1 region.…”
Section: Infrared Spectramentioning
confidence: 99%